2010
DOI: 10.3892/mmr.2010.393
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the biological significance of transthyretin as a biomarker for cutaneous T-cell lymphoma by its protein interaction partners

Abstract: Abstract. We previously identified transthyretin (TTR) and its posttranslational modifications as a down-regulated marker in mycosis fungoides (MF), a benign subtype of cutaneous T-cell lymphoma (CTCL). In order to more precisely understand the biological role of TTR in the etiology of MF, it is essential to clarify the pathways of progression by identifying further interacting proteins. This study is the first to combine blue native polyacrylamide gel electrophoresis (BN-PAGE) with surface enhanced laser deso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…As early as 2005, Schweigert and Sehouli found that TTR levels in serum of patients with early OC markedly changed ( 18 ).The levels in serum and ascites of OC patients were dramatically different ( 19 ). The differential expression of TTR had important biological significance in the development of cutaneous T-cell lymphoma ( 20 ). Katare et al found four mutations of TTR gene in LC rats, which changed three amino acids at positions 61, 100 and 115 ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…As early as 2005, Schweigert and Sehouli found that TTR levels in serum of patients with early OC markedly changed ( 18 ).The levels in serum and ascites of OC patients were dramatically different ( 19 ). The differential expression of TTR had important biological significance in the development of cutaneous T-cell lymphoma ( 20 ). Katare et al found four mutations of TTR gene in LC rats, which changed three amino acids at positions 61, 100 and 115 ( 21 ).…”
Section: Discussionmentioning
confidence: 99%